Red-shift of carbon nanotube surface plasmon EEL features utilising a dielectric filling - Seepujak, A; Bangert, U; Harvey, A (2006)
Simulations of the dynamical polarisability of a MWCNT (multi-wall carbon nanotube) by primary STEM electrons were performed. The simulations demonstrated eigenenergy modification (red-shifting), ascribed to the presence of a MWCNT dielectric filling, of coupled pi-surface plasmon EEL (electron energy-loss) features. Experimental EEL spectra of MWCNTs were acquired utilising a Gatan Enfina system attached to a dedicated STEM. These spectra confirmed the eigenenergy modification predicted by the model. In a filled MWCNT, an eigenenergy modification of a coupled pi-surface plasmon feature, redshifted from similar to 5.7 eV to similar to 4.4 eV, was experimentally validated. Red-shifting of this feature down to the visible frequency regime was not possible, owing to eigenenergy modification not occurring at the coupled limit. The eigenenergy modification phenomenon is remarkable since it is only one factor, namely whether or not a MWCNT is filled with a dielectric, that allows the plasmon energy to be red-shifted.